Type I ancient compact solutions of the Yamabe flow. (May 2016) - Daskalopoulos, Panagiota; del Pino, Manuel; King, John; Sesum, Natasa
Abstract: We construct new ancient compact solutions to the Yamabe flow. Our solutions are rotationally symmetric and converge, as t → − ∞, to two self-similar complete non-compact solutions to the Yamabe flow moving in opposite directions. They are type I ancient solutions.